SWOT and VPC analysis in R3 building shop in Palaran - Syalka Fitra Baihaqi; Eva Chintiana; Arifah Sofiyani (Enrichment : Journal of Management, 2026)
This research assesses the business development strategy of building materials store in Samarinda using SWOT analysis and Value Proposition Canvas (VPC). The impetus for this study stems for the growing impact of digital transformation in the retail industry, which compels small and medium enterprises to adapt in order to maintain their competitive edge. The methodology employed in this research is descriptive qualitative, untilizing a case study approach focused on the R3 Building Materials Store in the Palaran District. Data was gathered through observation, comperehensive interviews, and documentationsubsequently analyzed using Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) to ascertain the store’s strategic position and costumer value mapping via VPC. Results indicate strengths in personal customer interactions, competitive pricing, and advantageous location; weaknesses in digital operations and promotion; and opportunities from rising building material demand, infastructure development, and accessible digital technology. Practically, this study shows that traditional building materials retailers can improve their competitiveness by adopting affordable digital strategies, including social media promotionas, a simple inventory management system, and sameday delivery services. Managerially, these findings suggest that through a SWOT analysis and Value Proposition Canvas (VPC) enables small retailers to make more effective, customer centric strategic decisions in the digital era